WACANA RISALAH DAN PUTUSAN PERADILAN MAHKAMAH KONSTITUSI REPUBLIK INDONESIA - Triwati Rahayu (LITERA, 2009)
This study aims to describe discourse structure aspects, discourse-makingcomponents, and discourse context of judicial minutes and verdicts by Mahkamah Konstitusi Republik Indonesia. The focus was on the discourse of judicial minutes and verdicts by Mahkamah Konstitusi Republik Indonesia regarding the test of the substance by DPD on Keppres No. 185/M/2004. The study was conducted by employing the discourse analysis approach, in terms of the micro-structural and macro-structural aspects. The conclusions are as follows. First, the structure of theminutes consists of the cover, information, and content, while that of the verdicts consists of the title and number, heading, inquirer and responder data, problems, responses, problem focuses, judge verdicts, different opinions, and signatures. Second, the discourse-making components in the judicial minutes and verdicts by MKRI comprise long sentences, legal language registers, parallelisms, honorifics, repetitions, and conjunctions. Third, the discourse context consists of the history of the existing conflicts among DPD, the government, and DPR, and the context of the minutes and verdicts based on the social context.